War crimes and organized crime groups: problems from the congruence principle and the competence for their judgment (2018)
Although there are disparate theoretical positions on the nature of the organized crime groups currently operating in Colombia, the hermeneutical rules of the Constitutional Court’s jurisprudence establish that it is possible for these groups to commit crimes against persons and property protected by international humanitarian law (also IHL), that is, war crimes. With respect to these crimes, the competence for the objective factor - in its aspect of the nature of the matter - corresponds to the criminal judges of the specialized circuit. However, given the diffuse nature of the relationship between organized crime and armed conflict, it would not be unusual for the prosecutor to lie in the determination of the nomen iuris and charge for a common crime, and not for a war crime. The article seeks to answer the question of what solution should be adopted in these events. The proposal presented here is that the judge should opt for the declaration of nullity from the presentation of the indictment, as a way of harmonizing the guarantees of the defendant with the rights of the victims.